‘Marginalizing’ health: employing an equity and intersectionality frame - Deepa Venkatachalam; Gargi Mishra; Adsa Fatima; Sarojini Nadimpally (Saúde em Debate, 2020)
ABSTRACT The understanding that the drivers of inequities are multiple and intersecting is critical for health policy formulation and implementation. An intersectionality analysis reveals these relationships and allows a nuanced grasp of how health inequities are framed and understood. Using global statistics and other examples, the paper argues the significance of an intersectionality analysis in unravelling the disproportionate impact of inequity and the implications for the health and lives of persons experiencing these multiple discriminations. Attention to this, challenges the assumption of homogeneity and helps to visibilize lived realities. A few examples of acts of resistance are cited by the authors that have attempted to amplify the voices and knowledge of those whose realities are otherwise invisibilized by prevailing inequities, policies and discourses. ‘Marginalizing’ health thus implies an intersectional understanding of inequity as well as challenging and changing prevailing socio-political structures.